Trauma-focused ACT : a practitioner's guide to working with mind, body & emotion using acceptance & commitment therapy - Harris, Russ (Oakland, CA : Context Press, an imprint of New Harbinger Publications, Inc., 2021)
"Trauma-Focused ACT presents a highly effective, research-based protocol for treating post-traumatic stress disorder (PTSD), as well as a broad range of trauma-related disorders-from depression to addiction. Newcomers and experienced professionals alike will learn a comprehensive approach to treating trauma with a focus on living in the present, healing the past, and building the future. This unique guide is based on the empirically supported program author Russ Harris developed for the World Health Organization (WHO)"--
The many masks of trauma -- An ACT model of trauma -- Fight, flight, freeze, flop -- Keeping it safe -- The choice point -- The journey ahead -- Firm foundations -- Anchors away -- Flexible sessions -- Slipping in the shackles of fusion -- Heavy lifting -- Leaving the battlefield -- Making contact, making room -- Self-compassion -- Knowing what matters -- Doing what works -- Undermining problematic behavior -- Overcoming barriers, maintaining change -- When things go wrong -- Compassionate, flexible exposure -- The flexible self -- Working with the body -- Sleep, self-soothing, and relaxation -- Working with shame -- Moral injury -- Suicidality -- Finding the treasure -- Building better relationships -- Supporting the "younger you" -- Exposure to memories -- Grieving and forgiving -- The path ahead -- TFACT as a brief intervention -- Parting words.
Keywords: ACT; Psykoterapeut-patientrelationer; Posttraumatiskt stressyndrom; Psychotherapist and patient; Acceptance and commitment therapy; Post-traumatic stress disorder